The ICA evolutive position on international crisis, the example of the Russian invasion of Ukraine. Issue 1 (1st December 2022) - Fricker, David
Abstract : Established in 1948, in the aftermath of a World War immediately followed by the Cold War, the ICA promoted a neutrality that reflected the fears and values of a world exposed to clashes between geopolitical blocs and the terror of nuclear weapons. As the world has evolved, so has the ICA, reflecting the priorities, diversity and ambitions of its members. Increasingly, our members have addressed important social issues that impact on the preservation and use of records and archives. The resolution of support for Ukraine adopted by the ICA Executive Board on 10 March 2022 reflects this development as it is the role of the ICA to act responsibly and decisively in defense of records, archives, our profession and its members.